Numerical Modeling of Inclined Dense Jets in Stagnant Water on a Sloped Bottom - Wang, Xinyun (Université d'Ottawa / University of Ottawa, 2020)
Desalination plants are becoming essential due to the limited water resources in order to reduce the pressure of high demand of freshwater in many countries in recent decades. A concerning problem associated with desalination plants is the high concentration brine which has high risk to marine environments. Inclined dense jets are commonly used to treat brine produced by desalination plants or in industrial outfall discharges. They are produced when the brine is discharged at an upwardly inclined angle through a pipe or a diffuser system. Previous studies have mainly focused on jets on a horizontal bottom. In the present study, the influence of sloped bottom is investigated by numerical simulations using a modified solver in OpenFOAM (pisoFoam). Four different Reynolds Averaged Navier Stokes (RANS) turbulence models (Realizable k-ε, Standard k-ε, RNG k-ε and Nonlinear k-ε were employed to assess the accuracy of the selected turbulence models in predicting the jet behavior. Jets of inclination angle of 30° with four different initial conditions (Froude number=15, 20, 25, 30) on three different bed slope angles (2°, 5°, 10°) in stagnant water were conducted. Although inclined dense jets of the discharge angel of 60° are more common in discharge systems, sometimes they cannot be used in shallow waters in order to prevent surface pollution. In such cases, a relatively small jet inclining angle can be used to prevent the surface pollution and as shown in this thesis, bed slope can enhance the brine mixing and dilution. The results showed that Realizable k-ε model is more accurate among the turbulence models studied herein. The dilution at the impact point can be estimated based on the Froude number and initial conditions. After the impact point, the slope did enhance the dilution of the plume compared to the horizontal bed. The dilution was thus affected by the slope and the dilution after the impact point on the slope appeared to be linearly related to the distance to the source. Besides, the slope could enhance the jet dilution up to 20% compared with the horizontal bed after the impact point.
Keywords: Inclined dense jet; Sloped bottom